Neighbourhood social capital: measurement issues and associations with health outcomes. (January 2016) - Mackenbach, J. D.; Lakerveld, J.; van Lenthe, F. J.; Kawachi, I.; McKee, M.; Rutter, H.; Glonti, K.; Compernolle, S.; De Bourdeaudhuij, I.; Feuillet, T.; Oppert, J.‐M.; Nijpels, G.; et al.
Summary: We compared ecometric neighbourhood scores of social capital (contextual variation) to mean neighbourhood scores (individual and contextual variation), using several health‐related outcomes (i.e. self‐rated health, weight status and obesity‐related behaviours). Data were analysed from 5, 900 participants in the European SPOTLIGHT survey. Factor analysis of the 13‐item social capital scale revealed two social capital constructs: social networks and social cohesion. The associations of ecometric and mean neighbourhood‐level scores of these constructs with self‐rated health, weight status and obesity‐related behaviours were analysed using multilevel regression analyses, adjusted for key covariates. Analyses using ecometric and mean neighbourhood scores, but not mean neighbourhood scores adjusted for individual scores, yielded similar regression coefficients. Higher levels of social network and social cohesion were not only associated with better self‐rated health, lower odds of obesity and higher fruit consumption, but also with prolonged sitting and less transport‐related physical activity. Only associations with transport‐related physical activity and sedentary behaviours were associated with mean neighbourhood scores adjusted for individual scores. As analyses using ecometric scores generated the same results as using mean neighbourhood scores, but different results when using mean neighbourhood scores adjusted for individual scores, this suggests that the theoretical advantage of the ecometric approach (i.e. teasing out individual and contextual variation) may not be achieved in practice. The different operationalisations of social network and social cohesion were associated with several health outcomes, but the constructs that appeared to represent the contextual variation best were only associated with two of the outcomes.